Protection of Trade Secrets Through Non-Disclosure Agreements Against Worker Violations - Putri, Putu Nadia Monica; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This article analyzes legal protection of trade secrets through the implementation of Non-Disclosure Agreements (NDAs), particularly in cases of employee violations. The study is based on Case Number 14/Pdt.Sus-PHI/2020/PN Dps as a case study to assess the effectiveness of NDAs within the scope of Indonesian labor law.Purposes of the Research: The purpose of this research is to examine the role of NDAs as legal instruments in protecting corporate trade secrets from breaches of confidentiality by employees, and to evaluate the binding power of such agreements in industrial dispute resolutions.Methods of the Research: This study employs a normative juridical method, using both case and statutory approaches. Data were obtained through a literature review of relevant regulations, jurisprudence, and case documents, analyzed qualitatively.Findings of the Research: The findings indicate that NDAs are legally valid as supplementary employment agreements that can safeguard corporate interests. However, their effectiveness depends heavily on the clarity of contractual clauses, their alignment with employment relations, and the willingness of employers to assert their rights in court. This study contributes to the development of trade secret protection concepts in Indonesia, particularly within the labor law domain, and highlights the need for more specific and comprehensive regulation of NDAs.